(3jJjeI GdOgQ aj eMGSf Cgd GdYUQs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s
(3ChdgG (B:s
(3GdMeO ddg NjQ eG HOF Hg GdcdGe CeG HYO aEf eMGSf CUfGa GdCOH cKjQI hfcJgG bdjdI hdeG cGf GdTYQ YeOI GdCOH hYde GdYQH GdbSe GdChd ai eMGSf CTYGQ GdMeOGf s
(3BNQgG (B:s
(3JfJgi HJQLeI YHjO Gddg Hf CMeO GdHdOi jJdhgG ai GdeLdOI GdKGfjI GdbSe GdKGfi ai eMGSf Cgd GdYQGb s
(3fSNI NRGFfjI GdeLdOI GdChdis
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B189s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs